Main trends in seafood supply and typology of the European markets - Girard S. (Seafood market studies for the introduction of new aquaculture products, 2002)
The dynamics and comparative analysis of aquatic food consumption in European countries have been studied using the food balance sheet method in the framework of the MASMANAP EU concerted action. The first part of the presentation is devoted to the review and assessment of the statistical databases used in the evaluation of apparent consumption for 8 countries. Following on this expertise and the setting up of relevant data series of primary production and foreign trade over the period 1988-1998, the main trends in aquatic food supply and the striking features of consumption per country have been analysed. This provided a first set of information on typology among the EU15 countries with regard to their respective dependence on domestic production and imports of fisheries and aquaculture resources, their export capacities, the indicators of domestic market size and the level of apparent consumption per capita expressed in equivalent landed weight.
Seminar of the CIHEAM Network on Socio-Economic and Legal Aspects of Aquaculture in the Mediterranean, 2001/06/21-22, Zaragoza (Spain)